Drug Resistance Patterns and Treatment Regimens in Drug-Resistant Tuberculosis: A study from Kathmandu, Nepal - Bajracharya, Mijala; Singh, Sanjeev; Shrestha, Sabin; Giri, Usha (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Multi drug resistance is a serious threat for high prevalence countries and may have some effect on low prevalence countries and it is defined as resistance to at least isoniazid and rifampicin. Drug resistance tuberculosis results from in sufficient chemotherapy and other many factors. DR-TB treatment regimen is longer which use second line medication with high toxicityMethod: A retrospective study in GENETUP, NATA was conducted and patient’s data were taken for past 2 years from mangsir 2076 to mangsir 2078. Purposive sampling was done for the study. SPSS 16 and Microsoft excel 19 were used for the analysis of our result obtained in our study.Results: Of total 374 TB cases, 109 DR-TB patients were enrolled, out of which 76 were male and 33 were female. Majority of patients i.e., 43 were in between the weight group 46-55 kg. High number of patients i.e., 47(43.1%) were in the middle-aged adult group (31-59). 7 patients were found to have HIV status positive and 7 were found to be diabetics. 50 patients were categorized as new and 59 were categorized as previously treated patients. 77 patients were MDR/RR TB, 30 were pre-XDR and 2 were XDR TB. 56 patients were prescribed LR1 regimen, 31 were prescribed LR2 and 22 were prescribed SSTR regimen. 92(84.4%) patients were successfully treated which included cured and completed case. 10.1 % patients died and 5.5% patients lost to follow up.Conclusion: In our study, majority of DR-TB patients were male and high number of patients i.e., 47(43.1%) were in the middle-aged group (31-59) The most common pattern observed was MDR/RR TB and maximum patient were prescribed LR1 treatment regimen.